Quality indicators in the intensity modulated/image-guided radiotherapy era. (December 2016) - Gabriele, P.; Maggio, A.; Garibaldi, E.; Bracco, C.; Delmastro, E.; Gabriele, D.; Rosi, A.; Munoz, F.; Di Muzio, N.; Corvò, R.; Stasi, M.
Highlights: Nowadays there are no specific indicators for IMRT//IGRT Radiotherapy techniques. Two structure, 10 processe and 2 outcome QIs were elaborated. Data from four Italian Centers were collected and used for validation. Seven indicators were completely new. A new standard is proposed for four indicators. Abstract: Purpose: To propose new Quality Indicators (QIs) for the Intensity Modulated(IMRT)/Image-Guided(IGRT) Radiotherapy techniques. Materials and methods: Two structure, 10 process and 2 outcome QIs were elaborated. A working group including Radiation Oncologist, Medical Physicist and Radiation Technologists was made up. A preliminary set of indicators was selected on the basis of evidenced critical issues; the criteria to identify more relevant and specific QIs for IMRT/IGRT were defined; structure, process and outcome QIs were defined. The elaborated indicators were tested in four Italian Radiotherapy Centers. Results: Fourteen indicators were proposed. Seven indicators were completely new while a new standard is proposed for four indicators based on Validation Centers (VC) data. No change was reported for 3 indicators. The indicators were applied in the four VC. The VC considered were able to respect all indicators except indicator 2 for one Center. Discussion and conclusion: QIs may provide useful measures of workload and service performances.